Enhancing professional development of internee through reflection in textile and apparel design - Umer Hameed,; Saima Umer,; Usman Hameed,; Irfan Gul, (Technium Social Sciences Journal, 2020)
Although our society is most dependent on the services of professionals, still the professions are facing problems with the reliability of knowledge in individuals. As there is an element of uncertainty in the minds of professionals. The same problem is being faced by design industry professionals. Juniors and students who have to ultimately work in an organization as professionals are so confused with the demands from the designers to fulfill needs of the tentative profession. Students of design often ask questions about their ability and power to take sound and responsible decisions to make an effective design to influence design industry. Students are aware of the complications of the design process, which follows a complete step by step process, from transforming an idea to a design of value that serves manufacturers as well as consumers. Designers have the responsibility to create aesthetic and functional design as well as to keep focus on sustainability and ethical side of design.